Text mining and visualization case studies using open-source tools - Hofmann, Markus (Computer scientist); Chisholm, Andrew 1959- (Chapman & Hall/CRC data mining and knowledge discovery series, 2016)
Text Mining and Visualization: Case Studies Using Open-Source Tools provides an introduction to text mining using some of the most popular and powerful open-source tools: KNIME, RapidMiner, Weka, R, and Python